Propuesta de un sistema alterno para la toma de PLT en pozos de bombeo mecánico del campo X de Ecopetrol S.A. (2020)
The purpose of this research is to look for alternative systems that allow production logging conveyance in rod pumped wells in field X, located on the Upper Magdalena Valley Basin (Colombia). To achieve this, first of all, a compilation of the information concerning the alternative systems mentioned previously, then, the absence of mechanical restrictions to convey a PLT in each study well was verified by developing a matrix with the necessary parameters to run a production log, subsequently, the simulation of each of this systems (by means of PipeSim software and the analytical method of Petrie et al) allowed to establish from the technical point of view those wells where the proposed systems may or may not be implemented, followed by the respective cost-benefit analysis to consider the necessary costs for the implementation of any alternative system and defining the most appropriate to convey PLT in field X.